Sling Training - Krohn-Hansen, L.; Berget, A. (Meyer & Meyer, 2013)
Sling training is a balanced whole body workout that produces results faster than normal training. This is functional fitness at its best: Agility, strength and balance. However, the most important thing is that you can feel the results of the loop training in daily life. Sling training is an athletic training method, exercising with a rope and loop system and your own body weight. The method is also known under the name suspension training. This form of training was originally developed for the U.S. Army to train in foreign missions, even without heavy weights, etc. the whole body. In 2003, a company has patented this form of training in the USA. In Europe, this kind of training is known since 2010. Since 2012, the Sling Training is also offered in many fitness-studios. Although it is a modern method of training, its roots lie far back in time. Several thousand years ago, the ancient Greeks invented the gym. Physical fitness was promoted and every Greek city had a gymnasium, an exercise room for training. The gymnastic rings or static rings were introduced by the Romans and used as part of military training. The movements at the gymnastic rings inspired some of the sling exercises. The physical therapists used the sling therapy for a long time, but the sling training has emerged only in the last seven years and has since than become more and more popular. The sling training is a functional and valuable training method and earns increasing popularity. The sling training enables a whole-body exposure. From head to toe many often neglected muscle strains become activated. Without guidance, it may be that you feel insecure about technology, body position and loads during the training. However, you have to train properly to achieve maximum results. Because of their years of experience, the authors Berget and Krohn-Hansen have realized that the sling training follows three main principles: active core muscles, perfect posture and the 80/100 option. If you train with slightly bent hips, the load for the core muscles is reduced. This allows the beginner to try more exercises without tiring overall. If you can feel the strain in the abdominal muscles, you are on the right track - if your back hurts, you should take a break or choose a lighter exercise. The book contains 100 exercises from easy to difficult with 8000 variations. Each exercise is shown in detailed image-sequences that help with the correct execution. It also shows for each exercise, which muscles are involved. Every chapter leads from simple activation of individual muscles to total body exercises. Sling training features 15 sport-specific programs by excellent athletes, coaches and physical therapists that can improve your performance in a simple and fast way. The authors assume that simple repetition rate systems are as efficient as all sorts of other systems are. Anders Berget has worked in gyms and rehabilitation facilities with the sling training. He has also taught personal trainers in this area. Lennart Krohn- Hansen works as a trainer for the sling training. He has also developed a training program for an international training company.